2017
DOI: 10.1101/gr.212647.116
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive global genome dynamics of Chlamydia trachomatis show ancient diversification followed by contemporary mixing and recent lineage expansion

Abstract: Chlamydia trachomatis is the world's most prevalent bacterial sexually transmitted infection and leading infectious cause of blindness, yet it is one of the least understood human pathogens, in part due to the difficulties of in vitro culturing and the lack of available tools for genetic manipulation. Genome sequencing has reinvigorated this field, shedding light on the contemporary history of this pathogen. Here, we analyze 563 full genomes, 455 of which are novel, to show that the history of the species comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
180
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(203 citation statements)
references
References 50 publications
20
180
0
3
Order By: Relevance
“…Genovar E was highly predominant in our study as reported previously in other studies world‐wide (Gharsallah et al, ; Hadfield et al., ; De Vries et al., ). The conservation of genovar E may be the result of either increased fitness or simply be a stochastic process, reflecting the behavior of the hosts (Hadfield et al., ; Nunes et al., ; Satoh, Ogawa, Saijo, & Ando, ; De Vries et al., ). An expansion of genovar E occurred in Sweden and Europe, due to failure to detect this strain by certain commercial assays.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Genovar E was highly predominant in our study as reported previously in other studies world‐wide (Gharsallah et al, ; Hadfield et al., ; De Vries et al., ). The conservation of genovar E may be the result of either increased fitness or simply be a stochastic process, reflecting the behavior of the hosts (Hadfield et al., ; Nunes et al., ; Satoh, Ogawa, Saijo, & Ando, ; De Vries et al., ). An expansion of genovar E occurred in Sweden and Europe, due to failure to detect this strain by certain commercial assays.…”
Section: Discussionsupporting
confidence: 90%
“…The variability in the ompA gene has been known for a long time (Frost, Deslandes, Gendron, Bourgaux-Ramoisy, & Bourgaux, 1995;Sturm-Ramirez et al, 2000). A recent study investigating 563 full genome sequences of C. trachomatis reported that the ompA gene experiences the highest rates of recombination in the genome (Hadfield et al, 2017). The presence of mixed infections could be explained by the possibility of recombination and fast diversification of C. trachomatis strains.…”
Section: Comparison Of Genovar Distributions In Tunisian Patients Deter-mentioning
confidence: 99%
“…These values were derived using different software compared with that used previously (Joseph et al. 2016), hence these cannot be truly compared; the r / m value for C. suis is slightly greater than that seen in the recombinogenic C. trachomatis using the same method (0.31, Hadfield et al. submitted).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic variation in C. trachomatis, a highly prevalent bacterial STI [7], has historically been considered uncommon. However, a recent large-scale genomic analysis of geographically and temporally diverse C. trachomatis strains revealed a remarkable degree of homologous recombination and mutations that have occurred in the organism in the recent millennia [8].…”
Section: Discussionmentioning
confidence: 99%